The Influence of Independence and Audit Quality on the Integrity of Financial Reports on the Indonesia Stock Exchange - Yonson Pane; Frengky Situmorang (Outline Publisher, 2026)
Purpose: This study aims to determine whether independence and audit quality have a significant effect on the integrity of financial statements, both simultaneously and partially. Methods: The research methodology used is a quantitative descriptive method. The population in this study was all automotive companies listed on the Indonesia Stock Exchange. By using purposive sampling, a total sample of 11 companies was obtained for the period of 2013-2018. The study used secondary data obtained from financial statements of the automotive companies, as well as relevant theories and journals. Data were analyzed using multiple linear regression analysis methods. Results: The results of the research analysis show that independence and audit quality partially have an influence on the integrity of financial statements. Furthermore, independence and audit quality simultaneously also have an influence on the integrity of financial statements. Conclusions: Auditor independence and audit quality are significant determining factors that positively impact and ensure the integrity of financial statements produced by a company. Originality/value: This study provides specific empirical evidence regarding the impact of auditor independence and audit quality on financial statement integrity, focusing exclusively on the automotive industry sector listed on the Indonesia Stock Exchange over a comprehensive six-year observation period (2013-2018).